2021
DOI: 10.1016/j.bbih.2021.100337
|View full text |Cite
|
Sign up to set email alerts
|

Chronic circadian phase advance in male mice induces depressive-like responses and suppresses neuroimmune activation

Abstract: Altered working and sleeping schedules during the COVID-19 pandemic likely impact our circadian systems. At the molecular level, clock genes form feedback inhibition loops that control 24-hr oscillations throughout the body. Importantly, core clock genes also regulate microglia, the brain resident immune cell, suggesting circadian regulation of neuroimmune function. To assess whether circadian disruption induces neuroimmune and associated behavioral changes, we mimicked chronic jetlag with a chronic phase adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 84 publications
0
11
1
Order By: Relevance
“…An interesting follow-up study would be to subject adult Sdy mice to CJL to see whether these changes in behaviors are still seen or whether they are restricted to disruption during adolescence. In a previous study using a similar CJL procedure, male mice showed an increased depression-like behavior but no changes found in anxiety-like behavior in the elevated plus maze (Chen et al, 2021). This is in contrast to our mice exposed to CJL during adolescence, which show alterations of anxiety-like behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…An interesting follow-up study would be to subject adult Sdy mice to CJL to see whether these changes in behaviors are still seen or whether they are restricted to disruption during adolescence. In a previous study using a similar CJL procedure, male mice showed an increased depression-like behavior but no changes found in anxiety-like behavior in the elevated plus maze (Chen et al, 2021). This is in contrast to our mice exposed to CJL during adolescence, which show alterations of anxiety-like behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…At this stage, it is too early to know which (or all) of these outcomes contribute to the observed effects. However, a chronic phase advance circadian disruption model seems to reduce BDNF levels in the hippocampus ( Chen et al, 2021 ), suggesting that links between chronic circadian rhythm desynchronization and BDNF certainly extend beyond the SCN.…”
Section: Discussionmentioning
confidence: 99%
“…GCs regulate the expressions of clock genes in many regions of the brain (Bonaconsa et al, 2013;Chen et al, 2021;Leliavski et al, 2014;Spencer et al, 2018). Using a microdialysis probe inserted in both the jugular vein and the hippocampus in adult rats, Qian et al found that the free corticosterone in both compartments exhibited very similar rhythms (Qian et al, 2012).…”
Section: Cross Talk Between Gc Molecular Clock and Nf-κb In Neuroinfl...mentioning
confidence: 99%
“…However, since mouse and human tissues exhibit opposing patterns of expression of BMAL1 with respect to GC rhythm, extrapolating data from mouse models to human AD should be done with caution. Evaluating the role of GILZ in modulating inflammatory mediators in chronic jetlag represents another strategy to study the interrelationship between circadian rhythm, GILZ, and neuroinflammation (Chen et al, 2021;Shen et al, 2019). During health, release of GC is rhythmically in phase with CLOCK-BMAL1 transcripts with higher expression in the active phase (morning) and gradually decreasing reaching a nadir in the middle of the resting phase followed by gradual increase.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation